Analyzing the effects of four submerged macrophytes with two contrasting architectures on zooplankton: A mesocosm experiment - Lei Zeng; Biyun Liu; Zhigang Dai; Qiaohong Zhou; Lingwei Kong; Yi Zhang; Feng He; Zhenbin Wu (Journal of Limnology, 2017)
Increases in the structural complexity of submerged macrophytes are often shown to be linked to higher invertebrate abundance and diversity, but a number of studies have demonstrated, however, that this is not always the case. The objective of this study was to analyze the effects of four macrophyte species with two contrasting architectures (simple architecture with broad leaves: Vallisneria spiralis L. and Potamogeton malaianus Miq. and complex architecture with finely dissected leaves: Ceratophyllum demersum L. and Myriophyllum verticillatum L.) on zooplanktons. We hypothesized that structurally more complex macrophytes would support more zooplanktons and higher diversity, species richness, abundance and biomass, and to test our hypotheses, zooplankton samples within the above-mentioned macrophytes were collected to analyze the variances at different times. Contrary to our expectations, we found that the zooplankton’ responses were independent to the macrophyte architecture. Specially, although finely dissected M. verticillatum could significantly increase total zooplanktons, diversity, species richness, rotifers and cladocerans than the other three macrophytes, the effects of finely dissected C. demersum on these parameters exhibited no significant differences compared to two broad leaved macrophytes (V. spiralis and P. malaianus). Moreover, broad leaved macrophytes even increased more abundance zooplanktons than finely dissected C. demersum. In addition, the effects of macrophytes on zooplanktons also varied with zooplankton species. For example, the four tested macrophytes could significantly increase cladoceran abundance and biomass. Yet for copepods, the density was significantly increased in presence of V. spiralis and C. demersum, but P. malaianus and M. verticillatum did not show significant effects on copepod density. Moreover, all the tested macrophytes except for V. spiralis even significantly suppress copepod biomass. Therefore, our results did not support the hypothesis that structurally complex macrophytes harbor more zooplanktons, and showed that the effects of the investigated macrophytes on zooplanktons were not likely to depend on their architectures, but seemed to rely on complex relationships between macrophyte and zooplankton species.